Je suis un Italien de Paris: Italian migrants' incorporation in a European capital city. Issue 4 (12th March 2017) - Dubucs, Hadrien; Pfirsch, Thomas; Recchi, Ettore; Schmoll, Camille
ABSTRACT: Italy has experienced a new wave of population outflows, in particular since the end of the 2000s, with France as one of the top destinations. This paper investigates the structural and socio-cultural integration of Italian migrants in Paris. The paper is based on a mixed-methods approach, using in-depth interviews, census data and an online survey. We found that the profile and incorporation patterns of post-crisis migrants reflects a long-term trend of middling migration out of Italy. Similar to other studies, we show that current Italian migrants are prevailingly highly skilled and employed in non-manual jobs. As for socio-cultural integration, the paper highlights the symbolic value of the host city, to which migrants are strongly attached. Moreover, the longer the Italian's stay in Paris, the higher his/her integration in Italy-oriented activities, both within Paris and in Italy. This indicates a complex incorporation model that is at odds with assimilation but at the same time departs from ethnicised and community-based patterns. Italian migrants combine being both Parisian and Italian in a 'synergistic balancing act' (Erdal and Oeppen 2013. 'Migrant Balancing Acts: Understanding the Interactions between Integration and Transnationalism.' Journal of Ethnic and Migration Studies 39 (6):867–884.) of integration and transnationalism.